2018
DOI: 10.1063/1.5044380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inclined transverse jets on trailing-edge noise generation

Abstract: In this work, the effect of multiple transverse jets on the turbulent boundary layer developing over a flat plate is experimentally investigated for aeroacoustic purposes. A single line of jet nozzles with different spanwise spacings is located parallel to the trailing-edge of the plate, at approximately 30 jet diameters upstream of the trailing-edge. The axes of the jet nozzles have an inclination of 15 • with respect to the streamwise direction. Two values of the jet velocity ratio (r = u jet /u ∞) are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…The transducer sensitivity obtained from the calibration varied between 20.2 mV/Pa and 23.5 mV/Pa. The unsteady surface pressure measurements using FG transducers were carried out for 16 seconds using a sampling frequency of f = 2 16 Hz.…”
Section: Unsteady Pressure Measurements Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The transducer sensitivity obtained from the calibration varied between 20.2 mV/Pa and 23.5 mV/Pa. The unsteady surface pressure measurements using FG transducers were carried out for 16 seconds using a sampling frequency of f = 2 16 Hz.…”
Section: Unsteady Pressure Measurements Setupmentioning
confidence: 99%
“…The microphone has a flat frequency response at frequencies from 10 Hz to 10 kHz, with a dynamic range of 142 dB. The far-field noise spectra were computed for 16 seconds using a sampling frequency of f = 2 16 Hz. The acoustic data were recorded at a wide range of flow velocities of up to 40 m/s.…”
Section: Acoustic Measurements and Instrumentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While passive noise reduction methods have received a significant attention from the research community, active methods are in their early stages of development. Most commonly, previous works focused on the use of flow suction from 4, 38-40 , or flow injection into the boundary layer 41,42 . The main drawback of flow suction is that it requires a significant amount of air to be removed from the boundary layer, namely, it was found that removing approximately 60% of the boundary layer thickness provides the best aeroacoustic performance 40,43 .…”
Section: Introductionmentioning
confidence: 99%
“…Introduction T HE introduction of high bypass-ratio turbofans engines into civil aircraft have drastically reduced engine noise over the last several decades, making the airframe noise the same magnitude as that of the engine noise, especially during the landing phase. In order to reduce these prominent airframe noise sources several fundamental passive and active flow control methods have been investigated over the recent years, such as, morphing structures [1][2][3][4][5][6][7], porous materials [8][9][10][11], surface treatments [12], serrations [13][14][15] and transverse jets [16]. One of the prominent sources of airframe noises are the high-lift devices namely the slats and flaps.…”
mentioning
confidence: 99%